Herbicidal Activity of Thymbra capitata (l.) Cav. Essential Oil - Mercedes Verdeguer (Molecules, 2020)
The bioherbicidal potential of Thymbra capitata (l.) Cav. essential oil (EO) and its main compound carvacrol was investigated. In in vitro assays, the EO blocked the germination and seedling growth of Erigeron canadensis L., Sonchus oleraceus (l.) L., and Chenopodium album L. at 0.125 µL/mL, of Setaria verticillata (l.) P.Beauv., Avena fatua L., and Solanum nigrum L. at 0.5 µL/mL, of Amaranthus retroflexus L. at 1 µL/mL and of Portulaca oleracea L., and Echinochloa crus-galli (l.) P.Beauv. at 2 µL/mL. Under greenhouse conditions, T. capitata EO was tested towards the emergent weeds from a soil seedbank in pre and post emergence, showing strong herbicidal potential in both assays at 4 µL/mL. In addition, T. capitata EO, applied by spraying, was tested against P. oleracea, A. fatua and E. crus-galli. The species showed different sensibility to the EO, being E. crus-galli the most resistant. Experiments were performed against A. fatua testing T. capitata EO and carvacrol applied by spraying or by irrigation. It was verified that the EO was more active at the same doses in monocotyledons applied by irrigation and in dicotyledons applied by spraying. Carvacrol effects on Arabidopsis root morphology were also studied.